Megapolitan America : a new vision for understanding America's metropolitan geography - 497874 Nelson, Arthur C.; Lang, Robert E., 1959- (Chicago, Ill. : APA Planners ; London : Taylor & Francis [distributor], 2011)
Includes bibliographical references (p. [251]-261) and index